PENGARUH KONSENTRASI EKSTRAK AIR SEREH WANGI (Cymbopogon nardus L.) TERHADAP KUALITAS TAHU - Erynola Moniharapon; Sandriana J Nendissa; Agustina Souripet; Salma Hataul (AGRITEKNO: Jurnal Teknologi Pertanian, 2016)
The objectives of this research were both to know as well as to determine the exact concentration of lemongrass water extract applied during storage on the quality of tofu. A complete randomized experimental design with two factor of treatments was utilized. The first factor was concentration of lemongrass water extract with 3 levels of treatmens, i.e : T1 : 1 kg of lemongrass : 2 L of water, T2 : 1 kg of lemongrass : 3 L of water, T3 : 1 kg of lemongrass : 4 L of water. Whereas the second factor was the storage time, i.e : L0 : 0 day, L1 : 2 day and L3 : 4 day. Variables observed including chemical, and microbial. They consit of protein, moisture, TPC, and Salmonella. Results showed that lemongrass water extract with the concentration of 1 : 4 stored for 4 day had high protein and moisture, content which were 15.4%, and 74.37%, respectively results from microbial test showed that microbial growth was suspressed by the treatments and the content were still in the range set by Indonesian National Standard Agency.